High-frequency hydrodynamic and hydrochemical data from karst unsaturated zoneOREMEOREME - Leïla Serène; Guillaume Cinkus; Naomi Mazzilli; Jean-Baptiste Decitre; Christophe Emblanch; Franck Tison; Julien Dupont; Milanka Babic; Roland Simler; Matthieu Blanc (Data in Brief)
This dataset provides hydrological continuous data for 12 unsaturated zone flows of the Fontaine the Vaucluse karst system (France). These flows are caused by faults, fractures, karst conduits, and slow-flows from porous rock. This panel of unsaturated zone flow is unique. The dataset includes electrical conductivity, temperature and discharge, obtained through the artificial galleries of the Low Noise Underground Laboratory (LSBB, https://lsbb.cnrs.fr), and providing a unique window into the hydrological processes occurring in the unsaturated zone of karst aquifers. It also provides air pressure, temperature and humidity inside the galleries and weather parameters at the surface above the galleries (pluviometry, temperature, solar radiation, humidity, wind speed, wind direction, barometric pressure). The data are provided at an hourly time step from July 2022 to April 2024 and correspond to filtered data.Discharge is calculated from a homemade flowmeter consisting of a Plexiglas tube that collects the water and has a pressure sensor at the bottom. The pressure is converted into a volume of water thanks to a linear model, and then converted into discharge using the extreme values corresponding to the filling and emptying of the Plexiglas tube. All data have been filtered by removing erroneous values such as extremes due to probe malfunction or operator intervention, by checking the accuracy of the continuous measurement with point-in-time monitoring, and by removing values when the flow is inactive.This dataset is original in that it monitors various types of unsaturated zone flow, which are rarely monitored due to a lack of speleological access, especially slow flows within the limestone matrix. These data can be used to assess pressure transfer thanks to pluviometry, flow temperature and discharge; as well as mass transfer thanks to pluviometry and electrical conductivity. Weather data can also be used to improve climate models as the nearest weather station is 10km away.